The dynamics of linking permit markets - Katinka Kristine Holtsmark; Kristoffer Midttømme (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper presents a novel benefit of linking emission permit markets. We let countries issue permits non-cooperatively, and with endogenous technology we show there are gains from permit trade even if countries are identical. Linking the permit markets of different countries will turn permit issuance into intertemporal strategic complements. The intertemporal strategic complementarity arises because issuing fewer permits today increases investments in green energy capacity in all permit market countries, and countries with a higher green energy capacity will respond by issuing fewer permits in the future. Hence, each country faces incentives to withhold emission permits when permit markets are linked. Even though countries cannot commit to reducing their own emissions, or punish other countries that do not, the outcome is reduced emissions, higher investments, and increased welfare, compared to a benchmark with only domestic permit trade. We also show that permit market linking can arise as an equilibrium outcome.
Keywords: F55; Q54; 330; international agreements; permit markets; dynamic games; green technology investments